2016
DOI: 10.4236/oalib.1102422
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Adolescent Fertility among Rural Women of Ethiopia

Abstract: The main objective of this study is to identify the factors that contribute to adolescent childbearing and to examine to what extent these factors influence adolescent fertility of women in rural Ethiopia. This study was based on 2510 adolescent fertility data of rural women aged 15 -19 years that was extracted from the original women data of the 2011 Ethiopia Demographic and Health Survey (EDHS). Descriptive analysis, chi-square test and binary logistic analysis were employed. Hence, based on the result, reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
3
4
0
Order By: Relevance
“…Adolescents who were using contraceptives had a greater chance of having given birth. This was in line with other African studies which found out that teenagers who were currently using contraceptives had higher fertility [ 7 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Adolescents who were using contraceptives had a greater chance of having given birth. This was in line with other African studies which found out that teenagers who were currently using contraceptives had higher fertility [ 7 , 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…It is worth noting that despite marriage being the most important proximate determinant of fertility, being pregnant can also accelerate propensity to marry, hence a limitation of this study that needs to be examined. The finding was consistent with studies in Malawi, Ethiopia, Nigeria and Central Java which revealed that marital status had a positive effect on fertility [ 7 , 9 , 10 , 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…The majority of young women 20–24 years old who gave birth before the age of 18 lived in sub-Saharan Africa, 14 out of 15 countries that had high rates of pregnancies before the age of 18 [ 7 ]. Teenage pregnancy should be considered one of the major health concerns in every health-care system because it can lead to long-term complications of physical and psychological health, deteriorate economic and social status, and be a concern from both a human rights and a public health standpoint [ 8 , 9 ]. Pregnancy at an early age impacts future earning potential and leads to lifelong poverty [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 Teenage pregnancy should be one of the main issues in every healthcare system since early pregnancy can have harmful long-lasting implications on girls' physical, psychological, economic and social status 8 and it is a concern from both human rights and public health perspectives. 9 It is also a media-focal-point and a major issue irrespective of the teenager's marital status. 10 The global maternal mortality ratio (MMR) in 2017 is estimated at 211 deaths per 100,000 live births, showing a reduction of 38% since 2000.…”
Section: Introductionmentioning
confidence: 99%